2023
DOI: 10.1097/mao.0000000000004028
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cochlear Implant Satisfaction and Decisional Regret in Adult Cochlear Implant Users

Christian M. Shannon,
Kara C. Schvartz-Leyzac,
Judy R. Dubno
et al.

Abstract: Objective Determine associations expected and actual cochlear implant (CI) outcomes, decisional regret, and satisfaction in experienced adult CI users. Study Design Cross-sectional cohort study. Setting Tertiary medical center. Patients Thirty-nine adult CI users meeting traditional bilateral hearing loss indications with ≥12 months CI experience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A recent study from our research program underscores the importance of improving pre-CI counseling. We found that CI users have higher outcome satisfaction and less regret about their decision to undergo cochlear implantation when there is greater congruence between pre-CI expectations and post-CI outcomes (23). In the present cohort, 75% of patients had preoperative communication expectations that exceeded normative CIQOL scores for CI-users.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study from our research program underscores the importance of improving pre-CI counseling. We found that CI users have higher outcome satisfaction and less regret about their decision to undergo cochlear implantation when there is greater congruence between pre-CI expectations and post-CI outcomes (23). In the present cohort, 75% of patients had preoperative communication expectations that exceeded normative CIQOL scores for CI-users.…”
Section: Discussionmentioning
confidence: 93%